2015
DOI: 10.1371/journal.pone.0143588
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the Genetic Basis of Familial Aggregation of Pacemaker Implantation by a Large Next Generation Sequencing Panel

Abstract: BackgroundThe etiology of conduction disturbances necessitating permanent pacemaker (PPM) implantation is often unknown, although familial aggregation of PPM (faPPM) suggests a possible genetic basis. We developed a pan-cardiovascular next generation sequencing (NGS) panel to genetically characterize a selected cohort of faPPM.Materials and MethodsWe designed and validated a custom NGS panel targeting the coding and splicing regions of 246 genes with involvement in cardiac pathogenicity. We enrolled 112 PPM pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…We studied 88 articles, including 99 variants and 34 genes, after searching the PubMed database and identified 13 high-priority genes causing familial bradycardia, as follows: ABCC9 [18], ACTN2 [19], CACNA1C [20,21], DES [22][23][24][25][26][27], HCN4 [28][29][30][31][32], KCNQ1 [33,34], KCNH2 [35], LMNA [36,37], MECP2 [38], LAMP2 [39], NPPA [40], SCN5A [41][42][43][44][45], and TRPM4 [5,[46][47][48] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…We studied 88 articles, including 99 variants and 34 genes, after searching the PubMed database and identified 13 high-priority genes causing familial bradycardia, as follows: ABCC9 [18], ACTN2 [19], CACNA1C [20,21], DES [22][23][24][25][26][27], HCN4 [28][29][30][31][32], KCNQ1 [33,34], KCNH2 [35], LMNA [36,37], MECP2 [38], LAMP2 [39], NPPA [40], SCN5A [41][42][43][44][45], and TRPM4 [5,[46][47][48] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Given that we did not find any pathogenic/likely pathogenic variants using our Sanger approach, we used a custom NGS panel to look for variants in the coding and splicing regions of 246 genes associated with cardiovascular disorders in Lody’s whole blood and heart and Kitty’s whole blood DNA as described in the Methods section and in a previous study 22 . In total, using the human genome GRCh37/hg19 as reference, 20,756 variants were found in Lody’s whole blood DNA, 19,817 variants were found in Lody’s formalin-fixed paraffin-embedded (FFPE) heart DNA, and 20,040 variants were found in Kitty’s whole blood DNA.…”
Section: Resultsmentioning
confidence: 99%
“…A previously described custom next generation sequencing (NGS) panel containing probes for human DNA was used in the DNA from Lody’s whole blood and heart and from Kitty’s blood to sequence the coding and splicing regions of 246 genes associated with cardiovascular disorders including arrhythmias, cardiomyopathies, congenital heart defects, aortopathy, connective tissue disorders, Noonan spectrum disorders, pulmonary arterial hypertension, metabolic disorders that afflict the heart and lipid disorders 22 . Briefly, paired-end sequencing was performed using an Illumina MiSeq sequencer (Illumina, Inc., San Diego, CA), followed by read alignment using the BWA software, local realignment, base quality recalibration, and variant identification using the GATK software, and variant annotation using ANNOVAR 22 . A 300× average depth of coverage was obtained among variants for the three samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that mutant Kir6.2/SUR2B channels, but not Kir6.2/SUR2A or Kir6.1/SUR2B channels, had reduced sensitivity to MgATP inhibition, suggestive of K ATP overactivity in the endothelial cell subunit combination. In addition, the V734I variant was reported as a gain-of-function mutation in four early repolarization syndrome (ERS) patients with bradycardia 79 and in a patient with a permanent pacemaker who presented with isolated cardiac conduction disease 80 , perhaps consistent with K ATP channels playing a unique role in pacemaker and conduction system cells.…”
Section: Sur2mentioning
confidence: 99%